2018
DOI: 10.3390/ijms19041245
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Mediated Inflammation in the Pathogenesis of Intracranial Aneurysm and Subarachnoid Hemorrhage. Does Autophagy Play a Role?

Abstract: The rupture of saccular intracranial aneurysms (IA) is the commonest cause of non-traumatic subarachnoid hemorrhage (SAH)—the most serious form of stroke with a high mortality rate. Aneurysm walls are usually characterized by an active inflammatory response, and NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) has been identified as the main transcription factor regulating the induction of inflammation-related genes in IA lesions. This transcription factor has also been related to IA rupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 116 publications
(139 reference statements)
0
61
0
Order By: Relevance
“…Recent studies reported that HDCA3 inhibition appears to suppress NF-κB transcriptional activity by maintaining the NF-κB p65 acetylated (inactive) state and restraining the inflammatory response [33,43]. The NF-κB signaling pathway occurs in passive post-injury necrosis and in damaged cells, activating microglia to secrete inflammatory cytokines and causing amplification of the inflammatory response cascade [44,45]. In the present study, we found that levels of inflammatory cytokines (IL-1β, IL-6, and TNF-α) in brain tissue increased after SAH, associated with apoptosis (caspase-3, BCL-2), brain edema, and neurological defects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that HDCA3 inhibition appears to suppress NF-κB transcriptional activity by maintaining the NF-κB p65 acetylated (inactive) state and restraining the inflammatory response [33,43]. The NF-κB signaling pathway occurs in passive post-injury necrosis and in damaged cells, activating microglia to secrete inflammatory cytokines and causing amplification of the inflammatory response cascade [44,45]. In the present study, we found that levels of inflammatory cytokines (IL-1β, IL-6, and TNF-α) in brain tissue increased after SAH, associated with apoptosis (caspase-3, BCL-2), brain edema, and neurological defects.…”
Section: Discussionmentioning
confidence: 99%
“…Oestradiol supplementation/IL‐17A blockade reversed this effect (Hoh et al ., ). NF‐κB upregulates the expression of cytokines such as IL‐1, IL‐6, TNFα, chemokines (MCP‐1) and cell‐adhesion molecules (Aoki et al ., ; Saito et al ., ; Pawlowska et al ., ). Oestradiol suppresses the inflammatory responses of these pro‐inflammatory molecules by inhibiting NF‐κB activation and the subsequent autoregulated feedback loop (Ghisletti et al ., ; Jiang et al ., ; Xing et al ., ).…”
Section: Vascular Protective Role Of Oestradiolmentioning
confidence: 97%
“…5, 31 We asked whether inhibition of autophagy by CQ or 3-MA had any effect on CSE-induced migration and NF-κB activation of lung macrophages. 5, 31 We asked whether inhibition of autophagy by CQ or 3-MA had any effect on CSE-induced migration and NF-κB activation of lung macrophages.…”
Section: Inhibition Of Autophagy Abrogated Migration and Nf-κb Actimentioning
confidence: 99%
“…Previous studies found that autophagy mediated regulation of macrophage recruitment and NF-κB signalling pathway. 5,31 We asked…”
Section: Inhibition Of Autophagy Abrogated Migration and Nf-κb Actimentioning
confidence: 99%